Taxonomic review of the major larval pests of bolete fungi (Boletaceae) in Europe: The Pegomya fulgens, furva and tabida species groups (Diptera: Anthomyiidae) - Michelsen, Verner (Zootaxa, 2015)
A taxonomic review of the European species of the Pegomya fulgens, furva and tabida species groups is given with emphasis on characters of importance for the identification of males and females. These Pegomya species groups are represented in Europe by two, two and nine species, respectively. Their mycophagous larvae may all feed exclusively on bolete sporocarps of Leccinum and Boletus aff. edulis. Their relationships and biology are summarized. Each species is given a selective list of references and synonymy, richly illustrated descriptions of males and females, a list or summary of the examined material, and a synopsis of the known distribution and biology. Pegomya ringdahli sp. nov., previously confused with P. scapularis (Zetterstedt, 1846), is described from Fennoscandia. Lectotypes are designated for Anthomyia fulgens Meigen, 1826 and Pegomyia (Pegomyia) furva Ringdahl, 1938. An identification key is given to all 17 species (males and females) of Pegomya that supposedly feed as larvae on sporocarps of Boletaceae and Suillaceae in Europe.